COMPARISON OF THE USE OF TELEGRAM AND BLYNK PLATFORMS IN IOT-BASED GAS LEAK DETECTION - Apriliana, Anggie; Ichsan Pradana, Afu; Hartanti, Dwi (Jurnal Riset Informatika, 2025)
This study discusses the comparison between two Internet of Things (IoT)-based communication platforms, namely Telegram and Blynk, in a gas leak detection this system utilizes the NodeMCU ESP8266 microcontroller to detect hazardous functions to detect gas via the MQ-2 sensor, and measures temperature and humidity using the DHT11 sensor. Additional components such as buzzers, LEDs, relays, and exhaust fans are used as markers and early response when a leak occurs. The development of this system applies This study applies Waterfall method, which consists of planning, needs analysis, design, and implementation stages. This study then focuses on evaluating the effectiveness of both platforms, especially in the aspect. terms of notification speed, ease of integration, and data visualization. Testing is carried out by comparing the response system when detecting a gas leak and sending warning notifications via the Telegram and Blynk applications. This study concluded that Telegram is superior in sending notifications in real time, while Blynk provides advantages in visualizing sensor data and remote device control. In conclusion, the combination of using Telegram and Blynk in one system provides more optimal results than using one platform alone. This system has been proven to increase the effectiveness and efficiency in detecting gas leaks and providing early warnings to users quickly and interactively.